EEG and video documentation of benzodiazepine challenge in catatonic stupor: A case report - Hidetaka Tamune; Yu Tsukioka; Shota Sakuma; Daiki Taira; Yoshie Takaoka; Naoto Tamura; Tadafumi Kato (Wiley, 2024)
Abstract Introduction Catatonia, a psychomotor disorder characterized by diverse clinical signs, including stupor and mutism, remains elusive in its causes and a challenge to diagnose. Moreover, it is often underrecognized due to its resemblance to disorders of consciousness. However, when diagnosing catatonia, an antipsychotic medication may exacerbate the condition. The first‐line treatment typically includes benzodiazepines and/or electroconvulsive therapy (ECT). Case Report A 60‐year‐old woman with systemic lupus erythematosus (SLE) and epilepsy presented with catatonic stupor. Despite stable treatment, she experienced an acute deterioration in consciousness, requiring hospitalization. Her condition improved markedly following a benzodiazepine challenge, as documented on EEG. This improvement was short‐lived, but a second benzodiazepine challenge restored her from E1V1M1 (stupor) to E4V5M6 within minutes, as documented by a video recording. The patient was treated with lorazepam 1.5 mg/day orally and did not experience further relapses. Discussion The diagnosis of catatonia had been based on her scores on the Bush‐Francis Catatonia Rating Scale (BFCRS; Screening, 6/14; Severity, 19), despite meeting only two DSM‐5 criteria for catatonia (stupor and mutism). The diagnosis was supported by EEG and video documentation, excluding other potential differential diagnoses such as nonconvulsive status epilepticus and encephalopathy. Additional quantitative EEG analyses indicated that benzodiazepine administration increased brainwide alpha and beta band power significantly, suggesting that the benzodiazepine normalized attention, consciousness, and long‐range synchronization. This report additionally emphasizes the significance of video recordings in managing catatonia, and it helps in accurately tracking symptoms, documenting comprehensively, and improving patient understanding, which is crucial for treatment adherence.